2006
DOI: 10.1111/j.1423-0410.2006.00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of Leishmania donovani infantum in red cell suspensions by a flexible thiopyrylium sensitizer

Abstract: Leishmania is highly sensitive to photoinactivation under conditions that have been previously demonstrated to maintain RBC properties during 42 days of storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
(11 reference statements)
0
10
0
2
Order By: Relevance
“…Recently, using in vitro experiments several methods designed to inactivate Leishmania in blood products have been tested. These include the use of riboflavin (as a photosensitizer) and ultraviolet light [105], and the photochemical treatment by amotosalen plus ultraviolet light in platelet concentrates [106,107] as well as by thiopyrylium in RBC suspensions [108].…”
Section: Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, using in vitro experiments several methods designed to inactivate Leishmania in blood products have been tested. These include the use of riboflavin (as a photosensitizer) and ultraviolet light [105], and the photochemical treatment by amotosalen plus ultraviolet light in platelet concentrates [106,107] as well as by thiopyrylium in RBC suspensions [108].…”
Section: Preventionmentioning
confidence: 99%
“…This cross-linking makes the genome of pathogens no longer functional or able to replicate. The system has been successfully used to inactivate Leishmania in red cell suspensions [108].…”
Section: Preventionmentioning
confidence: 99%
“…Über DNA interkalierende Photoaktivatoren wie Thiopyrilium kann Leishmania nach Lichtbestrahlung um mehr als 5,7 log 10 TCID 50 inaktiviert werden [46]. Inaktivierung ist ebenfalls möglich durch Behandlung mit Psoralen und UV-Licht, wobei 4 log 10 reduziert wurden [47]; und mit Riboflavin und UV-Licht, wobei eine Reduktion von etwa 5 log 10 in Plasma und Thrombozytenkonzentraten erreicht wurde [48].…”
Section: A 42 Möglichkeiten Zur Abtrennung Und Inaktivierung Von Infunclassified
“…Previous studies have demonstrated that a DNA-intercalating flexible photosensitizer, thiopyrylium (TP), has potent activity against many viral and bacterial pathogens as well as the parasite, Leishmania donovani infantum, with little alteration of RBC storage properties under phototreatment conditions considerably more harsh than those required for robust pathogen inactivation [10,11]. In this study, we investigated whether TP can photoinactivate T. cruzi in RBC suspensions.…”
Section: Published In Final Edited Form Asmentioning
confidence: 99%